(untitled) (Forum Penelitian Agro Ekonomi, 2023)
The use of agricultural tools and machines (Alsintan) continues to be encouraged to support modern agriculture through diverse agricultural development programs. Alsintan is fulfilled through various schemes and project management. However, nationally, the use of Alsintan aid is considered not optimal. This paper aims to analyse the implementation of the Alsintan aid program and its benefits through the scientific review study method of various publications, regulations, and program policies, as well as the results of related studies. The review analysis method is carried out in a descriptive-qualitative manner from various associated data/information sources through the process of collecting, sorting, and grouping data and information to analyse the substance of the material. Some of the findings in this study are that among the existing aid programs, there are programs that are right on target and have impacts and benefits for users. Alsintan Service Business Group (UPJA) is one of the models still used/applied by the government, even though it faces various obstacles in its implementation. From the analysis results, at least two things must be considered in formulating the following strategy for Alsintan mechanisation aid: (1) procurement that must consider local suitability and needs (geographical and socio-economic), and (2) cross-sectoral policies should pay more attention to the possibility of developing the capability of the local machinery industry. The development of Alsintan must begin with identifying the needs of farmers, then increasing the agricultural business system efficiency, and finally leading to the commercialisation of farming businesses. This development pattern is expected to drive sustainable Alsintan aid.